Superhero kindergarten. Weirdo world [videorecording (DVD)] - Lee, Stan, 1922-2018; Schwarzenegger, Arnold; Heyward, Andy; Nicieza, Fabian (NCircle Entertainment, 2023)
The school day at Superhero Kindergarten is a lot like that at any other kindergarten... except these six extraordinary students have a secret. They are superheroes! Rather than powers derived from a radioactive spider bite or gamma rays, these special kids' powers are inspired by items commonly found in kindergarten classrooms across the globe including crayons, paste, putty and building blocks. And thankfully, they have Arnold Armstrong (AKA Captain Fantastic, the greatest superhero to ever live!) as their teacher (voiced by Arnold Schwarzenegger).